Passive, high-efficiency thermally-localized solar desalination. Issue 4 (30th March 2021) - Zhang, Lenan; Xu, Zhenyuan; Zhao, Lin; Bhatia, Bikram; Zhong, Yang; Gong, Shuai; Wang, Evelyn N.
Abstract : This review summarizes recent advances in passive thermally-localized solar desalination and provides a roadmap for more efficient, reliable, and commercially feasible solar desalination technologies. Abstract : Solar desalination holds significant promise for the water-energy nexus. Recent advances in passive solar desalination using thermal localization show great potential for high-efficiency freshwater production, which is particularly beneficial for areas without well-established water and energy infrastructure. However, there is a significant knowledge gap between laboratory scale innovation and commercial adoption. In this review, we discuss two critical factors – water production and reliability – which, if addressed systematically, could enable high-performance thermally-localized solar desalination systems. We show that optimizing heat and mass transfer of the entire device and recycling the latent heat of condensation are important to enhance total water production. Meanwhile, we discuss the potential of novel system architectures and fluid flow engineering to enable anti-fouling and robust desalination devices. In addition, we present techno-economic analysis that highlights the balance between water production, reliability, and cost. A criterion for economic feasibility is provided by comparing the price of desalinated water with commercially available bottle and tap water, which provides a roadmap for future development of solar desalination technologies.